THU0136 Confidence in the diagnosis of early rheumatoid arthritis: a prospective follow-up of 270 early-arthritis patients. (1st June 2001) - Berthelot, JM; Saraux, A; Le Henaff, C; Chalès, G; Thorel, JB; Hoang, S; Baron, D; LeGoff, P; Youinou, P
Abstract : Background: The treatment of early rheumatoid arthritis (RA) should not be delayed. However, aggressive therapy is often introduced only when rheumatogists feel confident enough in their diagnosis of RA. Objectives: We sought the confidence of both office-based-rheumatologists (OBR) and a college of 5 experts in their diagnosis of early-RA. Methods: 270 patients with early-onset (<1 year) arthritis were prospectively followed-up for 29 ± 11 months. At final examination, OBR and a college of 5 experts rated their confidence in the diagnosis of RA on 0–10 and 1–4 analogue scales respectively. Results: 35/270 patients (13%) were still unclassified by their OBR. RA was diagnosed in 114 (42%), spondylarthropathy in 56 (21%), and miscellaneous other disorders in 65 (24%). The OBR confidence in their final diagnosis of RA was 7, 5 ± 2, 3 (68/114 patients with a confidence of 8/10 or more). A collegial diagnosis of certain RA (N = 57) or probable RA (N = 41) was made for 98 patients. The strength of OBR confidence in the diagnosis of RA was strongly correlated to that of the college (r = 0, 892). Conversely, the fulfilment of 4 ACR criteria for RA since the first visit was associated with an only slight increase in final OBR confidence (7, 9 ± 2, 1). Conclusion: Although only 13/114 (11%) patients finally classified as RA changed from diagnosis during follow-up, the final confidence of OBR in their diagnosis of RA were below 8/10 in 40%, and was only slightly improved by the fulfilment of ACR criteria. This emphasises the need for a close follow-up of these patients during the first years and the use of RA criteria for the classification of early arthritis.